The contribution of digital marketing and marketing intelligence to the development of economic intelligence within service organizations: A case study of Algeria Post Corporation in the Wilaya of Tebessa - Abdelhalim, Lassoued; Abdelkayoum, Doumir Ammar; Mohammed, Lassoued; Nacima, Touati Tliba; Meriem, Hasnaoui (The International tax journal, 2025)
The study aimed to explore the relationship between digital marketing, economic intelligence, and marketing intelligence in improving the performance of Algeria Post Corporation. Digital marketing contributes to the creation of innovative electronic platforms for promoting and distributing products rapidly, providing direct feedback and accurate statistics that are used as core data in marketing intelligence systems. Through this integrated interaction, economic intelligence enhances strategic decision-making and increases the institution’s competitive capability.